Synthesis and Applications of Chiral Bicyclic Bisborane Catalysts - Yang, Zhao-Ying; Zhang, Ming; Wang, Xiao-Chen (Synthesis, 2022)
The development of chiral borane Lewis acid catalysts opened the door for transition-metal-free catalyzed asymmetric organic reactions. Herein, we have summarized our work on the preparation of two classes of novel chiral bicyclic bisborane Lewis acid catalysts derived from C2-symmetric [3.3.0] dienes and [4.4] dienes, respectively. These catalysts not only form frustrated Lewis pairs with Lewis bases to catalyze asymmetric hydrogenation reactions but also activate Lewis basic functional groups in traditional Lewis acid catalyzed asymmetric reactions.1 Introduction2 Synthesis of C2-Symmetric Fused Bicyclic Bisborane Catalysts and Their Use in Imine Hydrogenation3 Synthesis of Spiro Bicyclic Bisborane Catalysts and Their Use in N-Heteroarene Reduction4 Other Types of Asymmetric Reactions Promoted by Chiral Bicyclic Bisborane Catalysts5 Conclusion
Keywords: chiral borane; Lewis acid; frustrated Lewis pair; asymmetric catalysis; C2-symmetric; hydrogenation